An analysis of the impact of corruption on the realisation of the right to development. Issue 2 (4th May 2017) - Moyo, Khulekani
Abstract: Although the relationship between corruption and economic performance is now extant in the development literature, the nexus between corruption and its impact on the realisation (or non-realisation) of human rights is much less understood and therefore, in need of further elaboration. Emerging research appears to show a strong correlation between corruption, poverty, and inequality though this nascent research does not show any hierarchy among human rights affected by corruption. What is clear, however, is that when corruption becomes endemic in a polity, it benefits the well-connected and wealthy, debases the marginalised to lives of poverty and impoverishment. Inevitably, this leads to the weakening of the very accountability structures which are cardinal for protecting human rights. However, to date, no convincing theoretical framework has been advanced which seeks to explain corruption as a human rights violation. The traditional approach is to view corruption as impacting on, or contributing to human rights violations but not seeing it as a rights violation per se. Using the right to development as provided in the Declaration on the Right to Development and given legal teeth under the African Charter on Human and Peoples' Rights, as an entry point, this article argues that corruption is not only an obstacle to the realisation of the right to development, but a violation of human rights. Linking corruption and human rights, in particular, the right to development, as this article attempts to do, serves mostly to add a new perspective by deploying human rights norms and institutions in fighting the deleterious effects of corruption on the realisation of human rights.